ANALISIS KEMAMPUAN PASSING MENGGUNAKAN KAKI BAGIAN DALAM PADA PERMAINAN FUTSAL DI SMA NEGERI 1 PANGKEP - Atifah, Nur Indah; Hasmyati, Hasmyati; Azis, Ilham; hasanuddin, M. Imran; nurulita, retno farhana; hasyim, Muhammad qasash; Nawir, Nukhrawi (UNIVERSITAS NEGERI MAKASSSAR, 2023)
This study aims to analyze the analysis of the ability to pass with the inside of the foot in futsal games at SMA Negeri 1 Pangkep. This type of research is descriptive. The method used in this study is a survey method with data collection techniques using tests and observation sheets. The population in this study were students of class XI SMA Negeri 1 Pangkep. The sampling technique uses total sampling, so the number of samples in this study is 30 students. Data analysis uses quantitative descriptive as outlined in the form of a percentage. The results showed that the analysis of the ability to pass with the inside of the foot in futsal games at SMA Negeri 1 Pangkep was in the